2010
DOI: 10.1002/ajmg.a.33145
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic inheritance of adolescent idiopathic scoliosis: A study of extended families in Utah

Abstract: A heritability study of 69 extended Utah families with a history of adolescent idiopathic scoliosis (AIS) indicates that AIS is a polygenic, multifactorial condition. Each family reported a history of AIS within four generations; a total of 247 individuals were confirmed via X-rays and medical records to have AIS. Coefficient of kinship was more than 25 standard deviations higher for these 69 families than for the general population. Excluding all probands and assuming autosomal dominant inheritance, 1,260 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 34 publications
5
66
0
2
Order By: Relevance
“…When looking at the proportion of first-degree relatives having scoliosis, Wynne-Davies et al reported a prevalence of scoliosis in first-degree relatives of 6.9 % (10/144), Riszeborough et al 16 % (87/552) and Ward 24 % (372/1,513) [1][2][3]. We found a prevalence of scoliosis of 13 % (692/5,462) in first-degree relatives.…”
Section: Prevalence Of Scoliosis In Relativesmentioning
confidence: 43%
See 3 more Smart Citations
“…When looking at the proportion of first-degree relatives having scoliosis, Wynne-Davies et al reported a prevalence of scoliosis in first-degree relatives of 6.9 % (10/144), Riszeborough et al 16 % (87/552) and Ward 24 % (372/1,513) [1][2][3]. We found a prevalence of scoliosis of 13 % (692/5,462) in first-degree relatives.…”
Section: Prevalence Of Scoliosis In Relativesmentioning
confidence: 43%
“…Wynne-Davies et al [1] reported that 27.2 % of the study participants were having at least one first-degree relative with scoliosis. In a cohort of 82 surgically treated patients, Ward et al [3] found a relative with scoliosis within four generations in 69 of the pedigrees (82 %). The relatively high proportion of patients with one or more relative with scoliosis (any kind) and the high prevalence of scoliosis among first-degree relatives in our study compared to some of the earlier studies may partly be a result of a selection bias.…”
Section: Hereditymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the most common forms of kyphosis and scoliosis in adolescents are nonsyndromic and include: Scheuermann disease3 a form of nonsyndromic kyphosis, which affects >8% of the population12; idiopathic scoliosis (IS), which affects approximately 2% to 3% individuals13, 14, 15, 16; and congenital nonsyndromic scoliosis, which is reported to have a prevalence of approximately 0.5 to 1 per 1000 individuals 9. Familial and twin studies have indicated a genetic basis for kyphosis17, 18, 19, 20 and scoliosis,21, 22, 23, 24, 25, 26, 27, 28 with likely genetic heterogeneity. However, studies aimed at defining the genetic abnormalities causing these spinal disorders have been hampered by their phenotypic and genetic heterogeneity, variable modes of inheritance,8, 29 and gene‐environment interactions that may modify the phenotypic expression 9.…”
Section: Introductionmentioning
confidence: 99%